FDI and Corporate Geography in the Home Country - Rita Cappariello; Stefano Federico; Roberta Zizza (FIW - Research Centre International Economics, 2010)
This paper contributes to the empirical literature on the home-country effects of FDI. Instead of comparing FDI firms to non-FDI firms, we look at what happens within multi-plant FDI firms and we compare headquarters to onheadquarter plants belonging to the same firm. Using survey data on Italian industrial firms, we find that in FDI firms non-headquarter plants show a significantly worse performance in terms of employment and investment than headquarter plants. This suggests that the home-country effects of FDI tend to be biased in favour of headquarters.
Keywords: F20; F23; R30; 330; foreign direct investment; multi-plant firms; employment; Italy